2003
DOI: 10.1080/0954026031000136875
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol misuse by women

Abstract: Alcohol misuse among women is an important and growing problem. There is epidemiological and metabolic evidence that risk factors for and consequences of alcohol misuse are significantly different for women than for men. Understanding these differences is imperative if effective preventative and treatment interventions are to be undertaken. This article reviews the epidemiology of alcohol misuse by women, effects of alcohol misuse on women, fetuses, and relationships, and assessment and treatment strategies. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 121 publications
(121 reference statements)
0
4
0
3
Order By: Relevance
“…Women have less body water, less lean muscle mass, and lower levels of acetaldehyde than men, resulting in higher blood alcohol concentration from the same weight-adjusted level of alcohol consumption. A consequence of this is “the Telescoping Effect”: women demonstrating a shorter latency from onset of regular drinking to the development of alcohol related sequelae (Redgrave, Swartz, & Romanoski, 2003; Wilsnack et al, 1994). However, differences in the manner that women consume alcohol may mitigate some of these expected negative effects (Moos, Schutte, Brennan, & Moos, 2009).…”
mentioning
confidence: 99%
“…Women have less body water, less lean muscle mass, and lower levels of acetaldehyde than men, resulting in higher blood alcohol concentration from the same weight-adjusted level of alcohol consumption. A consequence of this is “the Telescoping Effect”: women demonstrating a shorter latency from onset of regular drinking to the development of alcohol related sequelae (Redgrave, Swartz, & Romanoski, 2003; Wilsnack et al, 1994). However, differences in the manner that women consume alcohol may mitigate some of these expected negative effects (Moos, Schutte, Brennan, & Moos, 2009).…”
mentioning
confidence: 99%
“…Studies have shown that female alcohol users experienced equivalent physical health consequences to males at lower quantities and frequencies (35)(36)(37). In the present study, almost the same proportion of females (30%) had alcoholic liver disease as males (28.57%) for lesser quantity and shorter duration of intake.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…There are differences between men and women in the course of substance use over time and in treatment response (Redgrave et al, 2003). In one study, older women had higher posttreatment abstinence rates than older men, based on a 6-month follow-up interviews with alcoholdependent patients in an outpatient program .…”
Section: Course and Progressionmentioning
confidence: 99%